2009
DOI: 10.1039/b906836h
|View full text |Cite
|
Sign up to set email alerts
|

Surface mediated synthesis of 2D covalent organic frameworks: 1,3,5-tris(4-bromophenyl)benzene on graphite(001), Cu(111), and Ag(110)

Abstract: The on surface synthesis of a two-dimensional (2D) covalent organic framework from a halogenated aromatic monomer under ultra-high vacuum conditions is shown to be dependent on the choice of substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
348
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(366 citation statements)
references
References 21 publications
15
348
2
1
Order By: Relevance
“…As was the case with TIPT, the structure of Figure 4a is different from that reported in the literature for the analogous molecule TBPB on HOPG, which features an oblique unit cell. 41 It is interesting to note that TIPT and TBPT networks on HOPG have same u vector despite the different size of the halogen atoms, which in turn leads to different v vectors and trimeric angles θ (for TBPT θ = 129 ± 6°, see Table 1). This may arise from a commensurability effect between the SAMNs and the substrate, which would also explain the discrepancies between the experimental and DFTcomputed molecular unit cells (Figure 1b and Figure 4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As was the case with TIPT, the structure of Figure 4a is different from that reported in the literature for the analogous molecule TBPB on HOPG, which features an oblique unit cell. 41 It is interesting to note that TIPT and TBPT networks on HOPG have same u vector despite the different size of the halogen atoms, which in turn leads to different v vectors and trimeric angles θ (for TBPT θ = 129 ± 6°, see Table 1). This may arise from a commensurability effect between the SAMNs and the substrate, which would also explain the discrepancies between the experimental and DFTcomputed molecular unit cells (Figure 1b and Figure 4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The packing differs from that reported in the literature for similar molecules TIPB and TBPB on HOPG. 41,46,49 This is attributed to stronger molecule···substrate interactions due to the presence of the triazine core, which makes TIPT and TBPT stiffer and planar precursors. Varying the solvents revealed that TBPT can form a bicomponent polymorph involving a hexameric R 6 6 (24) hydrogen-bonded arrangement of the solvent (heptanoic acid) molecules.…”
Section: ■ Conclusion and Perspectivesmentioning
confidence: 99%
“…15,[36][37][38] This leads in general to a second reaction step, the intermolecular Ullmann carbon-carbon coupling. 15,16,22,36,[39][40][41][42][43][44][45] Here, our initial aim was to utilize an on-surface chemical reaction to produce covalently bonded linear polymers. In order to characterize the structure of the unreacted monomer units, the I 2 TMTP molecule was deposited onto an Au(111) sample held at a temperature of approximately 30K with the C-I bond expected to remain intact upon molecular adsorption, due to the low temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is a timely issue to explore acetylenic coupling at interfaces, and recent studies using a sequential protocol with monolayer self-assembly followed by a crosslinking step provided encouraging results 11 . Pursuing a different vein, there is the prospective research domain dealing with on-surface covalent reactions under ultrahigh vacuum (UHV) conditions on clean metal surfaces to realize novel functional nano-architectures and networks [12][13][14][15][16][17][18][19] . However, many of the employed protocols imply appreciable activation barriers or rely on the enabling character of a set of leaving groups.…”
mentioning
confidence: 99%